Determinants of difficulty in activities of daily living in ambulatory patients undergoing hemodialysis - Takaaki Watanabe; Toshiki Kutsuna; Kei Yoneki; Manae Harada; Takahiro Shimoda; Yusuke Matsunaga; Norio Murayama; Ryota Matsuzawa; Yasuo Takeuchi; Atsushi Yoshida; Atsuhiko Matsunaga (Renal Replacement Therapy, 2018)
Abstract Background Patients undergoing hemodialysis (HD) have difficulty performing activities of daily living (ADL) compared to healthy people. ADL difficulty is an early predictor of loss of independence and mortality in older community-living people. However, determinants of ADL difficulty in HD patients have not been clarified. This study aimed to identify factors associated with ADL difficulty in ambulatory HD patients. Methods Subjects were 216 Japanese outpatients (130 men, 86 women; mean age, 67 years) undergoing maintenance HD three times a week. Clinical characteristics, depressive symptoms, motor function (leg strength, balance, and walking speed), and ADL difficulty related to lower-limb function such as mobility issues were compared across three difficulty levels (higher, middle, and lower) as classified according to the percentages of patients with perceived difficulty. Multivariate logistic regression analysis was performed to examine whether clinical characteristics, depressive symptoms, and motor function could discriminate ADL difficulty at each level. Receiver operating characteristic curve analysis was performed to determine cut-off values of motor function for predicting ADL difficulty at each level. Results ADL difficulty was independently associated with age (odds ratio (OR) = 1.05, 95% confidence interval (CI) 1.00–1.10; P = 0.039), presence of depressive symptoms (OR = 4.24, 95%CI 1.13–15.95; P = 0.033), and usual walking speed (OR = 0.94, 95%CI 0.90–0.97; P < 0.001) for higher level difficulty; age (OR = 1.06, 95%CI 1.02–1.10; P = 0.006), maximum leg strength (OR = 0.97, 95%CI 0.94–1.00; P = 0.043), and usual walking speed (OR = 0.96, 95%CI 0.93–0.98; P = 0.001) for middle level difficulty; and age (OR = 1.06, 95%CI 1.02–1.10; P = 0.006) and usual walking speed (OR = 0.93, 95%CI 0.90–0.6; P < 0.001) for lower level difficulty. Cut-off values of usual walking speed for predicting ADL difficulty for higher, middle, and lower level difficulty were 83.7, 75.5, and 75.1 m/min, respectively. Conclusions A slow walking speed and old age were significantly and independently associated with ADL difficulty in ambulatory HD patients. Presence of depressive symptoms was significantly and independently associated with ADL difficulty at the higher level of difficulty in ambulatory HD patients. These findings provide useful data for planning effective therapeutic regimens to prevent ADL difficulty in ambulatory HD patients.